Design and implementation of a low cost and portable tactile stimulator br - Kazma, Coskun; Levent, Vecdi Emre; Cardak, Merve; Aydin, Nizamettin (Tubitak Scientific & Technological Research Council Turkey, 2022)
When central nervous system has a problem, somatic area I and II respond to stimulation differently. Therefore, it is possible to identify some of the central nervous diseases when somatosensory on the fingertip is stimulated and responses are recorded and analyzed. We designed a system to stimulate the mechanoreceptors on fingertips. It is composed of a mechanical system for fingertip stimulation, an embedded controller, a control computer, and a software to control overall operation. During test, mechanoreceptors are stimulated according to the test protocols. Individuals' answers are recorded to be evaluated by the developed software. In this study, several design approaches for embedded controller were also examined and an FPGA based controller with the same functionality but higher performance was implemented. A test procedure was performed on 51 individuals at the department of pediatric psychiatry in a hospital, to investigate whether the sex has an effect on attention deficit and hyperactivity disorder.
Keywords: Microcontroller; FPGA; tactile stimulator; neuroscience; ADHD; NEUROSENSORY ASSESSMENTS; SOMATOTOPIC ORGANIZATION; DEVICE; ACTIVATION; PRESSURE; CHILDREN; SII; Computer Science; Engineering